2020
DOI: 10.1002/kin.21471
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies on the reaction of H atom with C3H6

Abstract: A comprehensive study on the reaction of H + C 3 H 6 has been conducted in order to clarify the temperature and pressure dependence of product branching. Site-specific rate of addition of a hydrogen atom to the center carbon is measured by a comparative method for the evolutions of H atoms behind reflected shock waves. The rate constant for the addition to the center carbon can be given by ln(k 1-2 /cm 3 molecule-1 s-1) =-(1.67 ± 0.65) × 10 3 T-1-(24.18 ± 0.55) for H + C 3 H 6 → n-C 3 H 7 * → products (T = 106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…The rate constant for terminal addition (black) is approximately a factor of 2 faster than that calculated here. However, as mentioned by Chen et al, 20 the higher values reported by Miller and Klippenstein may be attributed to input data errors. An error in symmetry number affects the energy barriers and pressure-dependent rate constant expressions.…”
Section: Theoretical Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…The rate constant for terminal addition (black) is approximately a factor of 2 faster than that calculated here. However, as mentioned by Chen et al, 20 the higher values reported by Miller and Klippenstein may be attributed to input data errors. An error in symmetry number affects the energy barriers and pressure-dependent rate constant expressions.…”
Section: Theoretical Resultsmentioning
confidence: 84%
“… High-pressure limiting rate constant comparisons for the reactions of Ḣ atom addition to propene. Solid lines represent the current work (ROCCSD(T)/aug-cc-pVXZ); dotted lines, Curran; 59 dashed lines, Miller and Klippenstein; 18 dashed-dotted lines, Chen; 20 ■, Seakins et al; 23 △, Watanabe et al; 27 ○, Kurylo et al. ; 26 ◀, Harris et al; 31 and □, Kerr et al 24 …”
Section: Theoretical Resultsmentioning
confidence: 99%
See 3 more Smart Citations